Effect of an icing medium containing the alga Fucus spiralis on the microbiological activity and lipid oxidation in chilled megrim (Lepidorhombus whiffiagonis). (January 2016) - Miranda, José M.; Trigo, Marcos; Barros-Velázquez, Jorge; Aubourg, Santiago P.
Abstract: The present study provides a first approach on the employment of an icing medium including Fucus spiralis, an alga exhibiting antimicrobial and antioxidant activities, for the preservation of fish quality during chilled storage. For it, two different concentrations of a F. spiralis extract (0.67 and 2.50 g lyophilized alga L −1 aqueous solution; F-1 and F-2 batches, respectively) were tested as icing medium for the chilled storage of megrim ( Lepidorhombus whiffiagonis ) for 14 days. The effects of the alga were compared with a counterpart batch stored in traditional ice prepared only from water (F-0 batch). A significant (p < 0.05) inhibition of microbial activity (aerobes, psychrotrophs, proteolytic bacteria, lipolytic bacteria; pH and trimethylamine formation) in F-1 batch and, especially in F-2 batch, was concluded. Concerning lipid oxidation development, a significantly (p < 0.05) lower formation of interaction compounds (fluorescence assessment) in samples corresponding to the F-2 batch was also observed, proving the inhibitory effect of F. spiralis on the formation of tertiary lipid oxidation compounds in chilled megrim. The icing medium proposed in this study may open the way to the development of a natural biopreservation strategy for chilled seafood based on algae. Highlights: An extract of the alga Fucus spiralis was used as icing medium. Microbial activity was partially inhibited by alga presence. The formation of tertiary lipid oxidation compounds was slowed down. The study opens the way to obtain seafood of higher quality and safety.